TSH Receptor Reduces Hemoglobin S Polymerization and Increases Deformability and Adhesion of Sickle Erythrocytes - Evelyn Mendonça-Reis; Camila Cristina Guimarães-Nobre; Lyzes Rosa Teixeira-Alves; Leandro Miranda-Alves; Clemilson Berto-Junior (Anemia)
SCD is a hereditary disorder caused by genetic mutation in the beta-globin gene, resulting in abnormal hemoglobin, HbS that forms sickle-shaped erythrocytes under hypoxia. Patients with SCD have endocrine disorders and it was described that 7% of these patients have clinical hypothyroidism. Recent studies have shown that mature erythrocytes possess TSH receptors. Thus, we aimed to assess the effects of TSH on SCD erythrocytes. The experiments were conducted using different concentrations of TSH (1, 2, 3, and 5 mIU/L). In HbS polymerization assay, erythrocytes were exposed to TSH in hypoxia to induce polymerization, and measurements were taken for 30 minutes. The deformability assay was made using Sephacryl-S 500 columns to separate deformable from nondeformable cells. Static adhesion test utilized thrombospondin to assess erythrocyte adhesion in the presence of TSH. TSH at all contractions were able to reduce polymerization of HbS and increase deformability. The static adhesion of erythrocytes at the lowest concentrations of 1 and 2 mIU/L were increased, but at higher contractions of 3 and 5 mIU/L, static adhesion was not modulated. The results suggest that TSH has potential involvement in the pathophysiology of sickle cell disease by inhibiting HbS polymerization, positively modulating deformability and impacting static adhesion to thrombospondin.